Lornoxicam drug—A new study of thermal degradation under oxidative and pyrolysis conditions using the thermoanalytical techniques, DRX and LC-MS/MS - Carvalho, A. C.S. [UNESP]; Zangaro, G. A.C. [UNESP]; Fernandes, R. P. [UNESP]; Ekawa, B. [UNESP]; Nascimento, A. L.C.S. [UNESP]; Silva, B. F. [UNESP]; Ashton, G. P.; Parkes, G. M.B.; Ionashiro, M. [UNESP]; Caires, F. J. [UNESP] (Elsevier, 2019)
In the present work, the thermal behavior of Lornoxicam drug was studied under oxidizing (air) and pyrolysis (N2) atmospheres using simultaneous thermogravimetry and differential scanning calorimetry (TG-DSC), differential scanning calorimetry (DSC), Hot Stage Microscopy (HSM) and Evolved Gas Analysis (EGA) in the form of thermogravimetry coupled to infrared spectroscopy (TG-FTIR) and mass spectrometry (TG-MS). The thermal degradation product formed at different temperatures were examined using liquid chromatography coupled to mass spectrometry (LC–MS) and Powder X-Ray Diffraction (PXRD). The thermal study showed that the drug does not melt, partially amorphized on heating, it is thermally stable to 205 °C and undergoes thermal decomposition in two overlapping mass loss steps. Furthermore, the DSC and MS techniques suggest that thermal degradation processes are very complex, which occur with the release of gaseous products HCN, SO2, COS, CO2, N2O and CO and formation of three intermediate in the thermal residue.
Keywords: EGA; HSM; LC–MS/MS; Lornoxicam; Thermal degradation